Instructional Materials of Podcast Scripts in Bridging EFL Students’ Awareness of Climate Change: A Need Analysis - Faizah, Vivian Azarine; Inderawati, Rita; Eryansyah, Eryansyah (JOLLT Journal of Languages and Language Teaching, 2025)
The integration of global issues, such as climate change, into English reading materials is crucial in the Independent Curriculum. However, there is a gap in current teaching resources regarding the inclusion of climate change topics in an accessible and engaging format. This study, conducted at SMA Srijaya Negara in Palembang, Indonesia, aims to analyze students’ needs for climate change-based descriptive texts integrated into podcast scripts as supplementary teaching materials. Using a mixed-methods approach, the study involved questionnaires and semi-structured interviews with 35 tenth-grade students, their English teacher, and a stakeholder. The findings reveal that students need materials that align with their English proficiency levels and are relevant to global issues, especially climate change. Students expressed a preference for descriptive texts that are not only informative but also simple to understand, allowing them to connect the theme of climate change with their real-life contexts through engaging and relatable materials. This study identifies a significant gap in the existing teaching materials, as they do not fully accommodate students’ needs for climate change content presented in accessible descriptive text formats. Based on these findings, the study advocates for the development of climate change-based podcast scripts derived from descriptive texts, designed to match students’ English proficiency and be more relevant to their daily lives. This research is expected to contribute to the development of supplementary teaching materials that enhance students’ English skills while raising their awareness of climate change issues.